Legal Construction of Cumulative Decisions on Marriage Annulment and Divorce Claims at the Jakarta Religious High Court - Yani, Ahmad; Pakarti, Muhammad Husni Abdulah; Fathonih, Ah; Rosadi, Aden; Zakaria, Soni; Ridwan, Ahmad Hasan (Universitas Islam Negeri Raden Fatah Palembang, 2025)
The growing number of petitions for marriage annulment and divorce raises a complex legal challenge, as each is grounded in different legal purposes and carries distinct implications. This issue has emerged in several cases before the Religious Courts within the DKI Jakarta High Religious Court jurisdiction, notably Case Number 3000/Pdt.G/2023/PA.JS, where both claims were filed simultaneously. This study aims to analyze the legal construction and judicial reasoning of judges in deciding cumulative applications for annulment of marriage and divorce lawsuits in the Religious Court within the jurisdiction of the DKI Jakarta High Religious Court. This study adopts a descriptive–analytical socio-legal method, drawing on legal construction theory, judicial reasoning, law enforcement principles, and the doctrine of maslahah mursalah to critically analyze judges’ legal reasoning and judicial outcomes. Data were analyzed through normative legal analysis supported by case law. The findings reveal that the legal construction applied by judges in handling the accumulation of annulment and divorce claims prioritizes justice, legal certainty, and human rights protection by harmonizing procedural law with substantive Islamic legal principles. The novelty of this research lies in formulating a coherent legal solution that legitimizes the selective acceptance of claims, enabling courts to resolve procedural conflicts while safeguarding the legal status and post-divorce rights of wives and children. This approach offers a workable judicial framework for adjudicating comparable cases within the Religious Courts.